Perancangan Strategis Menggunakan Balance Scorecard Pada Framework Ward & Peppard (Studi Kasis WeChat Pay) - Ashfa Fikriya, Arina; Havid, Achmad; Zuchrotunisa; Deagita, Nisa’; Nisa, Sa’diatun (Universitas Hasyim Asy`ari, 2024)
WeChat Pay is a company focused on electronic financial services. Along with the rapid development of the digital era, many new e-wallets have emerged. To remain competitive and survive in an increasingly tight competition, WeChat Pay needs to formulate the right business strategy. One important step is to plan a strategy for the effective development of WeChat Pay. Therefore, the purpose of this paper is to develop a strategic plan for WeChat Pay that can contribute positively and innovatively in supporting the achievement of business strategy goals to enhance competitiveness in its services. This paper adopts the Ward and Peppard framework to plan information systems strategy and evaluate internal and external business environment factors. WeChat Pay’s business strategic planning is analyzed using the Balanced Scorecard, while the portfolio of WeChat Pay’s applications is mapped using McFarlan’s Strategic Grid Analysis. Ultimately, this paper provides recommendations for the organization, including: improving service performance, customer relationship management, employee training and certification, market expansion, and integration with other e-wallets.